Eksplorasi Sains Asli pada Pembuatan Kain Tenun Buton untuk Pembelajaran IPA Berbasis Etnosains - Julia Julia; Sigit Sujatmika; Ani Widyawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2021)
This study aims to explore ethnoscience at the stage of dyeing woven fabrics, recommending science teaching materials related to Buton woven fabrics, especially in natural dye additives, and inviting the public to preserve the culture of woven fabrics. Ethnoscience is the science that is used to understand how people's original knowledge in the process of dyeing woven fabrics can be constructed into scientific scientific knowledge. The dyeing of the weaving threads is still done traditionally by using materials obtained from nature. The research was conducted in the Colorful Weaving Village. This research is a qualitative descriptive research through the process of data reduction, data presentation, drawing conclusions, and verification. The research data collection was carried out through observation, interviews, and documentation. Triangulation of sources by comparing the results of interviews with journal sources and websites. The results showed that at the stage of dyeing Buton woven fabrics, they contained junior high school science concepts, namely plant classification, natural dye additives, substance particles, molecules, simple planes, energy changes, solution concentration, and physical changes that could be used in contextual science learning. in school.